Factor in Farmers' Decision-Making in Adopting Certified Seed as a Strategy to Mitigate Environmental Squeeze - Neng Elmi Salehah; Trisna Insan Noor; Reny Sukmawani (Universitas Galuh, 2026)
The use of certified seed in rice farming system has a significant contribution to increase crop productivity. Farmers would have a result in greater harvest yield by using high-quality seed compared with farmers who used uncertified seed. In contemporary society, as the challenge in environment grow rapidly, farmers are required to make adaptive and strategic choices. The use of certified seed represents a strategic choice since it possesses more reliable genetic and physiological quality. This research intended to identify the use of certified seed among farmers and to analyze the factors affecting farmers’ decisions to use certified seed. This research was conducted in Gegerbitung District, Sukabumi Regency, West Java. The method used by this research is quantitative descriptive with dual linear regression analysis, as the preliminary survey, it results there are 76% farmers in Gegerbitung District who already used the certified seed, the rest of the percentage, used uncertified seed with the distribution of varieties including Inpari 32 (59%), Ciherang (14%), Inpari 49 (2%) dan Local (24%). In greater detail, this study demonstrates the decision-making in the use of certified seed is significantly influenced by farming experience, whereas age, educational background, family dependent, and land size do not have a significant effect on the decision to use certified seed